Estratégias de fidelização de clientes: um estudo em uma empresa de software na cidade de Parintins/Am - Cunha, Thainá Barros (Brasil, 2023)
Currently, the market is becoming increasingly competitive, given the importance of using techniques or strategies that put companies ahead of their competitors and thus manage to satisfy their customers in search of loyalty. This study had as general objective to know what are the customer loyalty strategies that the software company from Parintins/Am adopts, highlighting its organizational structure, services, systems and target market, it also intends to identify the company's customers who are already loyal more than a year ago; know the reasons that led customers to remain loyal to the company and analyze the factors that influence customer loyalty to the company. This research was based mainly on theoretical sources from the author Philipe Kotler, Cobra (2005), Oliveira (2012) and among other authors who instigate the theme. The methodological procedures employed in terms of objectives are descriptive research, of an applied nature, with qualitative approaches, using case study procedures. The research had as a collection instrument the online questionnaire with closed questions applied to the software company's customers, being divided into two stages, the first stage aimed to collect customer data with the proposal to find the specific objectives already mentioned, in the second stage it was A questionnaire was applied to the company's manager in order to collect data that could correlate with the factors and reasons that it considers to lead to the customer loyalty process. The analyzes pointed to cultural, social, personal and psychological factors as influencers, the latter being the factor with the highest incidence of responses obtained both in the first stage of the questionnaire and in the second stage. Therefore, it is concluded that customer loyalty is determined by several factors that go according to the needs or desires of customers, determined by motivation or simply by social or cultural characteristics of the group to which they belong.